Assessing the Adjustment Implications of Trade Policy Changes Using the Tariff Reform Impact Simulation Tool (TRIST) - Brenton, Paul (2012)
TRIST is a simple, easy to use, country focused tool to assess the short-term adjustment implications of trade reform. It has been developed to improve the information available to policy makers in developing countries. It has the following key features: projections are based on revenues actually collected at the tariff line level rather than simply applying statutory rates, as in currently available tools; it is transparent, runs in Excel, with formulas and calculation steps visible to the user, and is open-source with users free to change, extend, or improve according to their needs; it has high policy relevance because it projects the impact of tariff reform on total fiscal revenue from imports (including VAT and excise taxes) and results are available at the product level so that sensitive products or sectors can be identified; the tool is flexible and can incorporate tariff liberalization scenarios involving any group of trading partners and any schedule of products. This paper describes the TRIST tool and provides a range of examples that demonstrate the insights that the tool can provide to policy makers on the short-term adjustment impacts of reducing tariffs.